Preanalytical Stability of CSF Total and Oligomeric Alpha-Synuclein - Abdi, Ilham Y.; Majbour, Nour K.; Willemse, Eline A. J.; van de Berg, Wilma D. J.; Mollenhauer, Brit; Teunissen, Charlotte E.; El-Agnaf, Omar M. (Frontiers in Aging Neuroscience, 2021)
Background: The role of cerebrospinal fluid (CSF) alpha-synuclein as potential biomarker has been challenged mainly due to variable pre-analytical measures between laboratories. To evaluate the impact of the pre-analytical factors contributing to such variability, the different forms alpha-synuclein need to be studied independently. Method: We investigated the effect of exposing CSF samples to several pre-analytical sources of variability: (1) different polypropylene storage tubes, (2) use of non-ionic detergents, (3) multiple tube transfers, (4) multiple freeze-thaw cycles, and (5) delayed storage. CSF oligomeric- and total- alpha synuclein levels were estimated using our in-house sandwich-based enzyme-linked immunosorbent assays. Results: Siliconized tubes provided the optimal preservation of CSF alpha-synuclein proteins among other tested polypropylene tubes. The use of tween-20 detergent significantly improved the recovery of oligomeric alpha-synuclein, while multiple freeze-thaw cycles significantly lowered oligomeric-alpha-synuclein in CSF. Interestingly, oligomeric alpha-synuclein levels remained relatively stable over multiple tube transfers and upon delayed storage. Conclusion: Our study showed for the first-time distinct impact of pre-analytical factors on the different forms of CSF alpha-synuclein. These findings highlight the need for special considerations for the different forms of alpha-synuclein during CSF samples’ collection and processing.